Making Progress in Marketing Research. Issue 4 (November 2017) - East, Robert; Ang, Lawrence
Progress in any subject requires the origination of theoretical ideas. Often, new theoretical ideas are derived from unpredicted findings. Some methods, such as surveys, yield more unpredicted findings compared to experiments and too great an emphasis on testing theories by experiment may therefore lead to fewer new ideas. We argue that researchers in marketing and other social sciences should give more consideration to methods that produce large amounts of evidence; by doing so, they may speed up the development of their subject.